Ethical Hacking Sebagai Strategi Keamanan Cyber di Era Digital: Studi Pustaka dan Implementasi Dasar - Kristofel Santa; Enjelita Radjakore; Rikna Aresta Lahutung; Ravila Putri Pangalila; Tresya Veronika Deil (Lembaga Pengembangan Kinerja Dosen, 2025)
Cyber security is becoming a crucial issue in the digital age, especially with the increasing number of cyber attacks on information systems in the public and private sectors. Ethical hacking or ethical hacking is one of the approaches that is beginning to be widely applied to identify and close security gaps in systems. This article discusses the basic concepts of ethical hacking, the process of its implementation, and its urgency in securing information systems. This study was conducted through a literature study approach from various academic and technical sources. The results show that ethical hacking can significantly reduce the potential for cyberattacks with a systematic preventive approach. The study also highlights the importance of legality and Ethics in its implementation, as well as the need for supportive policies at the institutional level.